Exposing Practical, Psychological, and Pedagogical Shadow Sides of Experiential Learning. (December 2018) - Wright, April; Hibbert, Paul; Strong, Ross; Edwards, Marissa
This article is based first-person experience with experiential learning (EL) practices in an undergraduate introductory management course. We consider how a challenging EL activity, based on volunteering during recovery from a catastrophic flood event, exposed three shadow sides of EL. These shadow sides of EL, which often remain hidden to educators, are practical, psychological, and pedagogical. We provide a characterization of each of these shadow sides and outline strategies for managing them. We also discuss the general applicability of our insights, including tentative theoretical extensions to Kolb's EL theory. We conclude by considering the potential for the shadow sides of EL to emerge in circumstances that are less confronting and extreme than those encountered by our students.